DC: a highly efficient and flexible exact pattern-matching algorithm - Deusdado, Sérgio (2009)
ware of the need for faster and flexible searching algorithms in fields such as web searching or bioinformatics, we propose DC - a high-performance algorithm for exact pattern matching. Emphasizing the analysis of pattern peculiarities in the pre-processing phase, the algorithm en- compasses a novel search logic based on the examination of multiple alignments within a larger window, selectively tested after a powerful heuristic called compatibility rule is verified. The new algorithm’s performance is, on average, above its best-rated competitors when testing different data types and using a complete suite of pattern extensions and compositions. The flexibility is remarkable and the efficiency is more relevant in quaternary or greater alphabets. Keywords: exact pattern-match, searching algorithms.